MODELING AND ASSESSING LAND-USE AND HYDROLOGICAL PROCESSES TO FUTURE LAND-USE AND CLIMATE CHANGE SCENARIOS IN WATERSHED LAND-USE PLANNING - Lin Yu.; Hong N.; Wu P.; Lin Ch. (My University, 2007)
Effective information regarding environmental responses to future land-use and climate change scenarios provides useful support for decision making in land use planning, management and policies. This study developed an approach for modeling and examining the impacts of future land-use and climate change scenarios on streamflow, surface runoff and groundwater discharge using an empirical land-use change model, a watershed hydrological model based on various land use policies and climate change scenarios in an urbanizing watershed in Taiwan. The results of the study indicated that various demand and conversion policies had different levels of impact on hydrological components in all land-use scenarios in the study watershed. Climate changes were projected to have a greater impact in increasing surface runoff and reducing groundwater discharge than are land use changes. Additionally, the spatial distributions of land-use changes also influenced hydrological processes in both downstream and upstream areas, particularly in the downstream watershed. The impacts on hydrological components when considering both land use and climate changes exceeded those when only considering land use changes or climate changes, particularly on surface runoff and groundwater discharge. However, the proposed approach provided a useful source of information for assessing the responses of land use and hydrological processes to future land use and climate changes.
Keywords: IMPACT ASSESSMENT; LAND-USE MODELING; HYDROLOGICAL MODELING; CLIMATE CHANGE; HYDROLOGICAL COMPONENTS; LAND-USE PLANNING POLICY; TAIWAN